Kombinasi Kecerdasan Intelektual? dan Kecerdasan Spiritual dalam Pendidikan Era Global - Biah Biah (Khazanah: Jurnal Studi Islam dan Humaniora, 2017)
The era development is something absolute. Each country must work together to improve the quality of their nation because the globalization is something that cannot denied. Along with globalization, the problem arose especially in education. Education that focuses only on the intellectual level of the output makes the output of education is getting away from traditional values , culture and nation religious value should be preserved. To counteract the negative effects of the globalization, it is required education that is not only pursuit intellectual of success but also combine them with spiritual intelligence. It is expected for the quality of graduates intellectually and spiritually.